نثر القرن التاسع عشر بين التقليد والتجديد (أحمد فارس الشدياق أنموذجاً) - سليطين وفيق; خضر يعرب (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
ينشد هذا البحث دراسة التقليد والتجديد في كتاب (الساق على الساق فيما هو الفارياق) بوصفه أنموذجاً للنثر في القرن التاسع عشر، إذ عمد الشدياق إلى أسلوب الكتابة التقليدية في التراث وأقام عليه نتاجه الأدبيّ وفقاً لموضوعات العصر المستجدّة بفعل الحراك النهضويّ، وخاصّة في النصف الثاني من القرن التاسع عشر عندما بدأت السلسلة الأدبية التقليدية، والأساليب الموروثة؛ من مكاتبات ديوانية، ورسائل، ومقامات، وغيرها بالتفكك لتظهر مكانها الأشكال الأدبيّة الجديدة من مقالة، ورواية، وقصّة، ومسرح نتيجة للتأثر بالغرب، وهذا أدى إلى ولادة أشكال كتابيّة هجينة تزاوج بين القديم والجديد، وتراوح بين التقليد والتجديد، فنجد الشدياق يكتب فنّ المقامة الموروث بأسلوب عصريّ، وموضوعات جديدة تنزاح بدرجة ما عن قواعد هذا الفنّ كما عرفه التراث العربي، وذلك نتيجة لمفاعيل النهضة العربية وما أفرزته من حراك ثقافيّ وفكريّ وأدبيّ. This research aims at studying the imitation and the renovation in the book AL-saq Ala AL-saq Fima Hwa Al-Fariaq as a sample of prose in the 19th century .He worked in a classical way about tradition and built his literary works on it, according to the latest objects as a result of the Renaissance movement. Especially in the second half of the nineteenth century even the traditional literary series (as a diueen writings, letters, maqamat…etc.) began the gradual discontinuation to be replaced by the new literary series (as article, novel, story, drama…etc.) as a result of the western effect. This led to the birth of new forms of hybrid writings that couple between the new and the old and varies between tradition and renovation. We find that Ashediaq writes Almaqama, which is an old heritage, in a modern style and new themes that differ in a way or another from the basics of this art as it was known in that Arabic tradition. That was a reaction of the results on the cultural, literal and intellectual movement.